Environmental regulation and its impact on welfare and international competitiveness in a Heckscher-Ohlin framework - Christian M. Scholz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
This paper discusses the issue of competitiveness and environmental regulation from the viewpoint of Heckscher-Ohlin models. It demonstrates that the impact of unilateral environmental regulations does not necessarily lead to a decrease in international competitiveness. Important is the measure of international competitiveness and the industry under consideration. Furthermore, this paper shows that in contrast to other theoretical work on this subject, unilateral environmental regulation does not necessarily lead to capital flight. It is also possible that the economy under consideration attracts more internationally mobile capital.
Keywords: Q20; 330; Umweltpolitik; Faktorproportionentheorem; Außenwirtschaftstheorie; Internationaler Wettbewerb; Standortwettbewerb; Kapitalmobilität; Theorie